THE EFFECT OF LIFE REVIEW THERAPY ON DEPRESSION IN THE ELDERLY AT UPT ELDERLY SOCIAL SERVICE BINJAI PROVINCE OF SUMATERA UTARA 2021 - Lindawati F. Tampubolon; Ance M. Siallagan; Deskrisman Stefan Mendrofa (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Life review therapy is one of therapy to reducing depression, building confidence, psychological well-being, and contentment in elderlylife. Purpose of this study was to analyze the effect of life review therapy on depression in elderly at Binjai erderly social service unit Province of North Sumatera 2021. This research method uses one-group pretest – posttest design. The sampling Technique was purposive sampling, with a sample of 30 respondents. The measuring instrument used by the Geriatric Depression Scale questionnaire. The results showed that the score before life review therapy is 7,20 (SD=2,592), and after life review therapy 4,13 (SD=2,825). Statistical test results show the life review therapy affected depression in elderly at Province North Sumatera Binjai erderly social service unit with paired t-test, ρ value = 0,001. This research is expected to be an alternative to reducing depression, improving well-being and quality of elderlylife.